Dairy intake in association with asthma symptoms among a large sample of children and adolescents: a cross-sectional study - Jamalvandi, Mona; Sasanfar, Bahareh; Nafei, Zahra; Behniafard, Nasrin; Jafari, Marjan; Salehi-Abargouei, Amin (Frontiers in Nutrition, 2024)
Background and Objective: Dairy products may be associated with an increased risk of asthma, although there is little scientific evidence to back this up. The goal of this study was to explore the association between dairy consumption and asthma symptoms.This cross-sectional study was conducted on children and adolescents aged 6-8 and 13-14 living in central Iran. Dietary food consumption was assessed using a multiple-choice questionnaire. Logistic regression was used to obtain odds ratios for the association between milk, other dairy products, and total dairy consumption with risk of asthma symptoms.In total, 7667 participants (3414 boys and 4253 girls) were included in the current study. Milk intake and total dairy consumption were not associated with the likelihood of wheezing, asthma confirmed by a doctor, current asthma, and asthma medication use. Also, there was no association between other dairy product intake and odds of wheezing in the past 12 months in the crude model. But, after adjustment for several confounders, those in the top category had lower odds of wheezing in the past 12 months than those in the bottom category (OR: 0.58; 95% CI: 0.40-0.85).the consumption of dairy products other than milk, including cheese and yogurt, might reduce the likelihood of wheezing in children and adolescents.